Marketing Public Relations Subway Indonesia Mengampanyekan Produk Ramah Lingkungan - Junaedi Junaedi; Rustono Farady Marta; Helen Olivia; Achmad Budiman Sudarsono; Risqi Inayah Dwijayanti (Jurnal Nomosleca, 2025)
Plastic takes hundreds of years to decompose in nature, leading to a buildup of waste that is difficult to manage. As a restaurant that produces a significant amount of plastic waste, Subway has launched a campaign to reduce plastic usage.  This study aims to explore how Subway Indonesia's Marketing Public Relations (MPR) campaigns promote environmentally friendly products. The theoretical foundation used in this study is Strategic Environmental Communication by Robert Cox. Strategic environmental communication refers to the practice of communication designed with a clear purpose, primarily to influence how people think and act regarding environmental issues. This research adopts a qualitative approach, based on a constructivist paradigm, using a case study method with a descriptive nature. Data collection techniques include observation, interviews, and documentation. The findings reveal that Subway’s MPR communicates environmentally friendly messages directly to customers through the role of operational staff. In addition, environmental campaign posters are also placed in strategic areas. Subway’s MPR activities in delivering environmental messages have successfully raised customer awareness about the global issue of excessive plastic use.